Hubungan Ibu Hamil Kekurangan Energi Kronik (Kek) Dengan Kejadian Resiko Stunting Di Empat Desa Lokus Stunting Wilayah Puskesmas Tambelangan - Faradisy, Rikhly; Nurhasanah, Nurhasanah (NHM PRESS, 2022)
Stunting is still a major nutritional problem in toddlers. Malnutrition occurs since the baby is in the womb and in the early days after the baby is born, however, stunting only appears after the baby is 2 years old. This study aims to analyze the relationship between KEK pregnant women and the incidence of stunting risk in 4 Stunting locus villages in the Tambelangan Health Center, Tambelangan District, Sampang Regency in 2020 - March 2021. This study uses a corrective analytic design with a retrospective approach, the population of all mothers and infants is 35 people. The sample is 35 respondents whose selection is done by total sampling. The independent variable is KEK pregnant women, the dependent variable is the risk of stunting. Data collection using secondary data from the maternal cohort and the MCH book for 2020 - March 2021, analyzed using Chi-Square test statistical analysis with a significance level of 0.05. The results showed that most of them had no history of SEZ during childbirth, namely 29 respondents (83%), most of the children under five were not stunted, namely 30 respondents (86%) and with a p-value of 1,000 > (0.05). Based on the results of this study, it can be concluded that there is no relationship between KEK pregnant women and the incidence of stunting. Mothers who have a history of CED during pregnancy with low education and knowledge have a higher risk of experiencing stunting.